AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN ALOKASI DANA DESA (ADD) DI DESA GADUNGAN KECAMATAN GANDUSARI KABUPATEN BLITAR - K, Bagus Ananda; Nurany, Fierda; Firmani, Silfa Diafatu (Publicio: Jurnal Ilmiah Politik, Kebijakan dan Sosial, 2024)
In accordance with Permendagri 113 of 2014 which regulates village financial reporting which must be managed based on the principles of transparency and accountability and implemented in an orderly and budgetary manner, this research examines the accountability and transparency of managing village fund allocations. . This research uses a qualitative descriptive methodology, collecting data through documentation and interviews. Based on Sugiyono's view, data analysis was carried out using documentation studies, field notes and interviews. According to Harbani Pasolong, the theory applied is the theory of Accountability and Transparency. Research findings show that although the governance of village fund distribution in Gadungan Village is generally good, there are still several problems that need to be improved. Proof of success includes the availability of media for reporting realization to the community which applies the principle of transparency, as well as the management of village fund allocation which involves the community in planning (Village Consultation), management and accountability which has implemented the principle of accountability. Keywords: Accountability, Transparency, Management, Village Fund Allocations